Conception and Feasibility of a Digital Tele-Guided Abdomen, Thorax, and Thyroid Gland Ultrasound Course for Medical Students (TELUS study) - Höhne, Elena; Recker, Florian; Schmok, Erik; Brossart, Peter; Raupach, Tobias; Schäfer, Valentin Sebastian (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose Medical education has been transformed during the COVID-19 pandemic, creating challenges regarding adequate training in ultrasound (US). Due to the discontinuation of traditional classroom teaching, the need to expand digital learning opportunities is undeniable. The aim of our study is to develop a tele-guided US course for undergraduate medical students and test the feasibility and efficacy of this digital US teaching method.Materials and Methods A tele-guided US course was established for medical students. Students underwent seven US organ modules. Each module took place in a flipped classroom concept via the Amboss platform, providing supplementary e-learning material that was optional and included information on each of the US modules. An objective structured assessment of US skills (OSAUS) was implemented as the final exam. US images of the course and exam were rated by the Brightness Mode Quality Ultrasound Imaging Examination Technique (B-QUIET). Achieved points in image rating were compared to the OSAUS exam.Results A total of 15 medical students were enrolled. Students achieved an average score of 154.5 (SD ± 11.72) out of 175 points (88.29 %) in OSAUS, which corresponded to the image rating using B-QUIET. Interrater analysis of US images showed a favorable agreement with an ICC (2.1) of 0.895 (95 % confidence interval 0.858 < ICC < 0.924).Conclusion US training via teleguidance should be considered in medical education. Our pilot study demonstrates the feasibility of a concept that can be used in the future to improve US training of medical students even during a pandemic.
Keywords: ultrasound education; tele-medicine; tele-ultrasound; course concept; medical students